2022
DOI: 10.3389/fpsyg.2022.898675
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Sports Participation and Curriculum Resource Utilization in Primary Schools Before and After the “Double Reduction”

Abstract: In order to eliminate capital chaos in the Education And Training (EAT) industry and ease parents' and students' excessive attention to subject achievements over physical quality, China government has launched the “Double Reduction” (“DR”) policy which promotes students' Sports Participation (SP) in the Compulsory Education (CE) stage concerning students' physical and mental health. Firstly, based on the actual situation of students' SP before and after releasing the “DR” policy, this paper understands the exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
(19 reference statements)
0
1
0
Order By: Relevance
“… 2 Secondly, in addition to banning students from using mobile phones, the cultivation of students’ physical quality and sports quality should be taken as the key content, and schools should expand physical education programs and cultivate students’ sports hobbies. 83 Thirdly, parents should guide teenagers to make the most of their time at home and strengthen the supervision on children’s mobile phone use and timely detect, stop and correct adolescents’ MPD. 84 Additionally, previous studies have found that the cause of MPD in individuals is not entirely due to the lack of realistic social support resources, but also may be due to the failure to make good use of existing social support.…”
Section: Discussionmentioning
confidence: 99%
“… 2 Secondly, in addition to banning students from using mobile phones, the cultivation of students’ physical quality and sports quality should be taken as the key content, and schools should expand physical education programs and cultivate students’ sports hobbies. 83 Thirdly, parents should guide teenagers to make the most of their time at home and strengthen the supervision on children’s mobile phone use and timely detect, stop and correct adolescents’ MPD. 84 Additionally, previous studies have found that the cause of MPD in individuals is not entirely due to the lack of realistic social support resources, but also may be due to the failure to make good use of existing social support.…”
Section: Discussionmentioning
confidence: 99%